Sonographic assessment of renal size and its correlation with anthropometric measures among indigenous population in Peninsular Malaysia - Khammas, Abdul Sattar Arif; Abu Hassan, Hasyma; Mohamad Ibrahim, Ramlah; Mohamad Nasir, Nurul Nadiah; Bahari, Norafida; Suppiah, Subapriya; Mohamad Saini, Suraini; Ibrahim, Idris; Zakaria, Mohd Hazeman; Mahmud, Rozi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Renal size measurement using ultrasound is a valuable parameter in the diagnosis of renal function and its diseases. This study is aimed to determine the differences of mean and correlation between the renal length (RL), renal width (RW) and renal parenchymal thickness (RPT) with age, gender and anthropometric measurements among indigenous population in Malaysia. Methods: A prospective cross-sectional study was carried out in this survey. Abdominal sonography was performed on 240 subjects. Sonography of the renal size included measurements of RL, RW and RPT. A portable ultrasound machine (Mindray DP-50, Shenzen, China) with a 3.5 MHz convex probe was used in this study. An independent-samples t-test, one-way ANOVA and Pearson's correlation coefficient test were performed in statistical analysis. Data were analyzed using SPSS program version 22.0. A P-value of <0.05 was considered significant. Results: The mean left RL was significantly decreased after the age of 54 years. RL of both kidneys was positively significant correlated with height (P<0.001), weight (P<0.001), waist circumference (WC) (P<0.001) and hip circumference (HC)(P<0.001). Similarly, a significant positive correlation was found between right RW and right RPT with weight (P=0.007 and P=0.003, respectively). Left RPT was significant correlated with height (P=0.006), weight (P<0.001) and HC (P=0.035). There was a significant positive correlation between left RW and height (P=0.048). A significant difference was also reported between right RL (P<0.001), left RL (P<0.001) and left RPT (P=0.040) with BMI. Conclusion: The normal values of renal size measurements are related to age, gender, height, weight, BMI, WC, and HC.